Exosomes derived from apical papilla stem cells improve NASH by regulating fatty acid metabolism and reducing inflammation - Yifei Nie; Wenqing Meng; Duanqin Liu; Ziqing Yang; Wenhao Wang; Huiping Ren; Kai Mao; Weipeng Lan; Chuanhua Li; Zhifeng Wang; Jing Lan (BMC, 2024)
Abstract Background Apical papilla stem cells (SCAPs) exhibit significant potential for tissue repair, characterized by their anti-inflammatory and pro-angiogenic properties. Exosomes derived from stem cells have emerged as safer alternatives that retain comparable physiological functions. This study explores the therapeutic potential of exosomes sourced from SCAPs in the treatment of non-alcoholic steatohepatitis (NASH). Methods A NASH mouse model was established through the administration of a high-fat diet (HFD), and SCAPs were subsequently isolated for experimental purposes. A cell model of NASH was established in vitro by treating hepatocellular carcinoma cells with oleic acid (OA) and palmitic acid (PA). Exosomes were isolated via differential centrifugation. The mice were treated with exosomes injected into the tail vein, and the hepatocytes were incubated with exosomes in vitro. After the experiment, physiological and biochemical markers were analyzed to assess the effects of exosomes derived from SCAPs on the progression of NASH in both NASH mouse models and NASH cell models. Results After exosomes treatment, the weight gain and liver damage induced by HFD were significantly reduced. Additionally, hepatic fat accumulation was markedly alleviated. Mechanistically, exosomes treatment promoted the expression of genes involved in hepatic fatty acid oxidation and transport, while simultaneously suppressing genes associated with fatty acid synthesis. Furthermore, the levels of serum inflammatory cytokines and the mRNA expression of inflammatory markers in liver tissue were significantly decreased. In vitro cell experiments produced similar results.